Stable isotope evidence of anthropocene disruption in African softshell turtle foraging - Willemien de Kock; Marcel T. J. van der Meer; Ronald van Bommel; Alberto J. Taurozzi; Matthew Von Tersch; Morten E. Allentoft; Meaghan Mackie; Max Ramsøe; Matthew Collins; Michelle Alexander; Per J. Palsbøll; Canan Çakırlar; et al. (PLoS ONE, 2026)
We examined the dietary habits of contemporary and Middle to Late Holocene (ancient) populations of African softshell turtles ( Trionyx triunguis ) from the northern Levant using stable isotope analysis (δ 13 C, δ 15 N, and δ 34 S) and ZooMS biomarker identification. Our study presents the first application of ZooMS to this taxon, facilitating species-level identification. Stable isotope values point to potential variation in T. triunguis diets, possibly reflecting changing ecosystem conditions. Modern turtles from the south-western Turkish coast exhibit relatively high δ 15 N values, but low δ 13 C values, likely influenced by human-provided carrion and agriculture-driven inputs. Ancient turtles (n = 4) from the Levant exhibit more diverse diets, with two individuals indicating a more pronounced marine foraging signature. These preliminary findings are consistent with increased anthropogenic influence on T. triunguis foraging in some regions. This study provides new biomolecular insights into the ecological history of T. triunguis , increasing our understanding of its (long-term) dietary plasticity and potential response to anthropogenic pressures.